Cita Rasa dan Keistimewaan Kerupuk Bontot Khas Karawang Jawa Barat - Rifa Aulliya Nurdian Salsabila (TOBA: Journal of Tourism, Hospitality, and Destination, 2023)
Bontot crackers are crumbs (leftovers) of prawn cracker ingredients that can no longer be cut with a cutting machine. Bontot itself in the Sundanese sense can be understood as the last (youngest). Bontot Kerupuk itself is unique in terms of name, method of manufacture and raw materials that make up the dish. Bontot is a typical food from the Karawang region which is not widely known but has its own taste. The purpose of this study was to find out the typical food of the Karawang area which is known to the public. The method used in this study is a synthetic research method. The results of this study indicate that Kerupuk Bontot has a distinctive taste and aroma during the manufacturing process. Bontot crackers are crumbs (leftovers) of prawn cracker ingredients that can no longer be cut with a cutting machine. Bontot itself in the Sundanese sense can be understood as the last (youngest). Bontot Kerupuk itself is unique in terms of name, method of manufacture and raw materials that make up the dish. Bontot is a typical food from the Karawang region which is not widely known but has its own taste.